Prevalence of GJB2 mutations in the Silk Road region of China and a report of three novel variants. (April 2014) - Du, Wan; Zhu, Yi Ming; Guo, Yu Fen; Wang, Qiu Ju; Liu, Xiao Wen
Abstract Conclusion: The c.235delC of GJB2 gene is the hotspot mutation of the hearing loss population in the Silk Road region of China. It is high time that some active interventions (such as hearing aids or cochlear implant) are provided to improve their language ability and quality of life. Objectives: The first gene to be identified for humans with nonsyndromic hearing loss was GJB2 gene. We investigated the prevalence of GJB2 mutations in the Silk Road region of China to study the mutation spectrum in this area. Methods: Bidirectional sequencing was carried out for all PCR products of samples. The statistical analysis was carried out using SAS 9.0.1 software. Results: Pathogenic mutations were identified in 243 of 2398 patients, including 168 homozygous mutations and 75 compound heterozygous mutations. Three variants (c.225G>T, c.521G>A, and c.557C>T) are novel mutations.